EFEITOS DA INFILTRAÇÃO DE VINHOTO DE CANA NO AQUÍFERO BAURU - RESULTADOS PRELIMINARES - REBOUÇAS, A.C.; BATISTA, R.P.; HASSUDA, S.; CUNHA, R.C.A.; POPPE, L.P. (Águas Subterrâneas, 1986)
RESUMO NAO DISPONIVEL